A calculation model for the overall process of high temperature corrosion mechanism induced by firing coal with high chlorine and sodium content. (15th August 2020) - Liu, Yacheng; Fan, Weidong; Guo, Hao
Abstract: The weight gain curve of corrosion test on metals is a common way to evaluate the degree of corrosion. In this paper, as opposed to the generally used experimental approach, a detailed calculation model was established to predict the corrosion weight gain curve. The model aims at determining the overall process of high temperature corrosion by combustion of coal characterized with high contents of chlorine and sodium. The calculation model focuses primarily on four steps: destruction of protective oxide layer; chlorination of alloying elements; diffusion and oxidation of metal chlorides; shedding of corrosion products. Sha Erhu coal with high contents of chlorine and sodium can cause severe fouling and slagging in boiler according to the reliable index of fouling factor RF . The mechanism of high temperature Cl-induced corrosion is generally called active oxidation. In the present work, a specific analysis of chemical kinetic calculation is carried out for each step of active oxidation mechanism. Besides, the calculation model involves destruction of protective oxide layer before the occurrence of active oxidation reaction and shedding of corrosion products after the corrosion mechanism. The lab-scale experimental results for the corrosion weight gain agree with the calculation model except for pure Cr at 610 °C, and it can be inferred that a low melting point eutectic involving Na2 CrO4 occurs. Furthermore, the protective oxide layer is initially formed on the substrate for TP347H (1Cr19Ni11Nb). But for T91 (10Cr9Mo1VNb), the protective oxide layer is not formed due to low content of Cr. The appearance microstructure and the elemental concentration distribution maps on alloy steel have been examined using scanning electron microscope coupled with an energy dispersive spectrometer (SEM−EDS) to provide an insight into material degradation. Highlights: A calculation model for chlorine corrosion during coal combustion is established. Occurrence of low melting point eutectic on substrate means severe degradation. Significantly higher corrosion resistance of TP347H than other alloy. Nickel-rich interface formed on substrate after corrosion due to low affinity.